Modified Anterior Superior Oblique Tuck: A Case Series. Issue 4 (1st October 2020) - Solanes, Federica; Velez, Federico G.; Robbins, Laura; Pineles, Stacy L.
ABSTRACT: Purpose: Selection of the ideal procedure to correct symptomatic excyclotropia depends on several factors including the degree of torsion and associated vertical, horizontal and pattern deviation. Selective tuck of the anterior temporal torsional fibers of the superior oblique (SO) tendon is an alternative procedure to the classical Harada-Ito. The purpose of this study is to report its stability and results. Methods: Retrospective review of all consecutive patients with symptomatic excyclotorsion of at least 5º (degrees) treated by selectively splitting and tucking the anterior temporal fibers of the SO tendon. Torsion in primary position was measured using the double Maddox Rods. Patients with additional symptomatic vertical or horizontal diplopia underwent simultaneous surgery on other extraocular muscles. Results: Five patients were studied. Mean age was 60 ± 8 years (47–67). Mean postoperative follow-up was 10 ± 8 months (3–21). The mean preoperative torsion of 11º±4º (7º-15º) significantly decreased to 3º±2º ( p = .03) at the first postoperative visit (16 ± 9 days) and 3 ± 2º during the last visit ( P = .03). The procedure corrected 1.4º±0.9º per mm of tuck. Postoperatively no patient complained of torsion. No undesirable vertical or horizontal deviations were noted. Conclusion: This technique is a simple alternative to manage symptomatic excyclotorsion, with significant and stable relief of moderate amounts of torsion and without inducing unexpected vertical or horizontal deviation.